General formulation and solution procedure for harmonic response of rigid foundation on isotropic as well as anisotropic multilayered half-space. Issue 70 (March 2015) - Lin, Gao; Han, Zejun; Li, Jianbo
Abstract: A general formulation and solution procedure are proposed for harmonic response of rigid foundation on multilayered half-space. It is suitable for isotropic as well as anisotropic soil medium. The wave motion equation is formulated in frequency wave-number domain in the state space. A hybrid approach is proposed for its solution, where the precise integration algorithm (PIA) is employed to carry out the integration. Very high accuracy can be achieved. The mixed variable form of wave motion equation enables the assembly of layers simple and convenient. The surface Green׳s function is regarded as rigorous, because it is free from approximations and discretization errors. The algorithm is unconditionally stable. The numerical implementation is based on algebraic matrix operation. Numerical examples of vibration of rigid foundation validate the efficiency and accuracy of the proposed approach. Graphical abstract: General formulation and solution procedure for harmonic response of rigid foundation on isotropic as well as anisotropic multilayered half-space. Highlights: A general formulation for wave propagation in multi-layered soil is proposed. The multi-layered soil can be isotropic as well as anisotropic. The PIA is proposed to solve the wave motion equation to ensure high accuracy. The effect of anisotropy of the soil on the SFI has been studied. The effect of anisotropy of the soil on the soil surface reaction has been studied.